Immunohistochemical expressions of adropin and inducible nitric oxide synthase in renal tissues of rats with streptozotocin-induced experimental diabetes - Kuloglu, T.; Aydin, S. (Taylor & Francis Ltd, 2014)
Diabetes is characterized by high blood glucose levels; it occurs in 30-35% of the population. Elevated glucose levels can damage a number of organs, including the kidneys. Several peptide hormones participate in maintaining glucose homeostasis including the recently discovered adropin, a 42 amino acid peptide hormone. Adropin also alters inducible nitric oxide synthase (iNOS) expression. Therefore, we studied how adropin and iNOS expression is altered in the renal tissues of streptozotocin (STZ) induced diabetic rats. Seven sham, seven control and seven Wistar albino male rats were fed standard rat pellets and water ad libitum for 10 weeks. The rats in the diabetic group were injected i.p. with a single dose of 60 mg/kg STZ dissolved in 0.1 M phosphate-citrate buffer, pH 4.5. After the 10-week experimental period, the rats in both groups were anesthetized and decapitated. Kidney tissues were excised and placed in 10% formaldehyde solution, taken through routine histological procedures, and embedded in paraffin. Sections 5-6 mu m thick were stained immunohistochemically using the avidin-biotin complex (ABC) method. Adropin and iNOS immunoreactivity were co-localized in the glomeruli, peritubular interstitial cells and peritubular capillary endothelium of the cortex; the thin limb of the loop of Henle in the medulla; and medullary peritubular interstitial cells and endothelium of the peritubular capillaries in both the control and diabetic groups. The intensities of adropin and iNOS immunoreactivity increased with the severity of the diabetes. Intense adropin immunoreactivity was detected in both the smooth muscle and human small intestine Paneth cells that were used as positive controls. The elevated levels of adropin and iNOS in the kidney indicates that these substances are involved in the pathophysiology of diabetes; this constitutes a compensatory mechanism against the damage inflicted by the disease.
Keywords: adropin; diabetes; immunohistochemistry; kidneys; nitric oxide synthase; streptozotocin